Gate-apps Number Plate Recognition untuk Sistem Akses Parkir Berbasis Internet of Things - Arnita; Budi Sunaryo; Putri Ramadina Daulay; Fikri Hasnul; Hidayat (Prosiding SISFOTEK, 2021)
Currently, the benefits of the internet of things can be felt in various fields of science and business, Gate-APPS is a product designed to increase the security and processing speed of internet of things-based parking access systems. Gate-APPS or Integrated Automatic Password Parking System is an embedded system or Embedded System designed to perform multiple verification functions. In this system, there are two identifications that are used as identification by the system to verify the status of the vehicle and the driver trying to access or exit the parking area. The main identification is carried out by an internet-based system by recognizing the vehicle number plate through the Image Processing process while at the entrance and exit gates. Double verification is carried out at the exit gate by means of a second identification by reading the driver's identity through the driver's ID Card which can also be used as a medium for parking fee transactions. The test results obtained indicate the success of vehicle number plate recognition is 85% and the overall system integration success is 100%. The average recording time was 3.88 ± 0.07 seconds for incoming access and 5.37 ± 0.03 seconds for outgoing access. The system is successfully integrated into a database server capable of storing and processing vehicle and driver identity data as well as historical parking access data. With these results, it shows that Gate-apps is able to be a solution to increase the security and processing speed of parking access systems.